(untitled) (Damascus University Journal of educational and Psychologyical sciences, 2024)
i The study aimed to reveal the degree to which teachers of the first cycle of basic education practice self-learning skills in Damascus education schools. To achieve the goal of the study, the researcher used the descriptive approach, and prepared a note card that consisted of (37) paragraphs, distributed over three main areas, namely: (self-learning planning skills, self-learning implementation skills, self-learning assessment skills), After verifying the validity and reliability of the study tool, the researcher applied it to an intentional sample of (37) male and female teachers from several schools in the city of Damascus. Medium, and the results of the study indicated that there were statistically significant differences between the average scores of teachers’ practice of self-learning skills due to the gender variable, and in favor of female teachers, while the results of the study indicated that there were no statistically significant differences between the average scores of teachers’ practice of self-learning skills due to the change in experience. In teaching, and in light of the results of the study, the researcher recommended the necessity of finding supportive and encouraging.